Expression of poly(Adenosine Diphosphate-Ribose) polymerase protein in breast cancer - Akanksha; Mishra, Shashi; Kar, Amrita; Karthik, J; Srivastava, Aviral; Khanna, Rahul; Meena, Ram (Journal of Mid-life Health, 2022)
Background: The use of poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors for breast cancer (BC) therapy is the subject of debate, and there is an urgent need to understand much the expression and prognostic role of the PARP1 protein. In this study, we have compared the expression of PARP between BC and benign breast disease (BBD) patients and also analyzed the association of PARP expression with clinicopathological parameters in BC. Methods: The study consists of 30 patients with newly diagnosed operable BC who were planned for surgery without neoadjuvant chemotherapy and 15 patients of BBD as a control between 2019 and 2021. Immunohistochemical analyses were performed prospectively on tissue samples. Anti-human PARP1 rabbit polyclonal antibody gives strong nuclear positivity. Internal control was the adipose tissue and the BBD acted as the external control. PARP1 expression was evaluated using the multiplicative quickscore method. Results: The mean age for BC patients was 51.30 ± 10.694 years (range: 25-75 years) while BBD was below 30 years. Overexpression of PARP was present in 25 (83.3%) and weak expression in 5 (16.7%) of BC patients compared to BBD, only 2 (13.3%) patients demonstrated an overexpression of PARP, and 13 (86.6%) patients showed weak expression which showed significant association (P < 0.001). In BC, nuclear PARP (nPARP) overexpression was seen in 22 (73.3%) patients and weak expression of nPARP in 8 (26.7%), whereas 5 (16.7%) patients showed cytoplasmic overexpression. On comparing expression of PARP with clinicopathological parameters, PARP overexpression was significantly associated with older population (age >50 years) (P = 0.002), postmenopausal women (P = 0.029), higher TNM stage (Stage II and III) (P = 0.014), higher histological grade (grade 2) (P = 0.043), and presence of lymphovascular invasion (P = 0.015). Enhanced PARP1 expression is closely correlated with positive estrogen receptor status (P = 0.001) and PR status (P = 0.001). Overall PARP and nPARP overexpression was significantly associated with ER- (P = 0.006 and P = 0.008) and PR-positive (P = 0.006 and P = 0.008) patients. The PARP and nPARP overexpression was significantly associated with nontriple-negative BC patients (P = 0.001 and P = 0.001). Conclusion: We have not come across any study in the literature to compare PARP expression in BC and BBD patients. On the basis of our observations, we concluded that PARP overexpression is a poor prognostic marker in BC.